A SOFTWARE SOLUTION TO WORK WITH A DATABASE OF BUSINESS PROCESS MODELS AND ANALYZE THEIR STRUCTURAL MEASURES - Kopp, Andrii; Orlovskyi, Dmytro; Liutenko, Iryna (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2022)
Business process modeling is one of the main tools of the BPM (Business Process Management) concept. With the help of business process modeling, business scenarios can be presented in the form of graphical models that can be easily understood by both information technology (IT) professionals and non-IT professionals – business analysts, software customers, department heads, top managers, and other stakeholders interested in business process improvement. Business process improvement is usually done through the automation of activities, which were identified as “bottlenecks” after analysis. However, it is possible to analyze a business process model only if it is clear and correct in terms of compliance with both the notation used and the real business process it depicts. This paper considers the analysis of BPMN (Business Process Model and Notation) business process model structural measures. It is assumed that business process models, which by their structural features violate rules of business process modeling, are neither understandable nor suitable for further work with them, which also can lead to various errors occurring at the stage of business process analysis, as well as at the stage of its improvement and implementation of proposed changes, i.e., during development, testing and maintenance of distinct software components, information system modules or BPM-system scenarios that ensure business process execution. Therefore, in this paper, we propose to identify the main elements of BPMN business process models and their structural measures that affect models’ understandability and maintainability and could be sources of errors. Considering selected measures, it is proposed to calculate respective values for a large collection of BPMN business process models, and then study compliance with theoretical business process modeling guidelines on practice when real business process models are designed. In order to provide efficient storage and processing of a large collection of BPMN business process models data, there were developed a database, and a software component. Results of analysis of BPMN business process model structural measures obtained using developed database and software component are demonstrated and discussed. The conclusion is made, as well as future research directions in this field are formulated.